Same-Sex Marriage from the Perspective of Legal Instruments, Human Rights and Hindu Religion - Putrawan, I Nyoman Alit; Widnyana, I Made Adi (Journal of Ecohumanism, 2024)
The purpose of this research is to analyse the anti-discrimination struggle against LGBT from a legal and human rights perspective and same-sex marriage from a Hindu legal perspective. This research is normative juridical research carried out using a statutory regulation approach and a legal concept approach. The analysis was carried out qualitatively. The phenomenon of same-sex marriage has indeed become controversial in various countries, including Indonesia. The struggle for anti-discrimination treatment for LGBT people has become one of the focuses of the human rights struggle. Various national and international legal instruments have regulated the right to equal treatment for everyone. However, this right cannot fully become the basis for legitimacy for the legality of same-sex marriage. Law Number 1 of 1974 concerning Marriage regulates that marriage is carried out by a man and a woman as husband and wife. Viewed from the perspective of Hindu law, the Manawa Dhramasastra states that marriage is carried out by a man and a woman to produce offspring.